Exploring The Intersection of Education and Business: Integrating Teacher Workload, Student Achievement, and Buddhist Perspectives on Science and Technology - Selvi Agustina; Tursinah Anggendari (JURNAL RISET MANAJEMEN (JURMA), 2023)
This qualitative research aims to explore the interconnectedness of education and business by examining the relationship between teacher workload, student achievement, and integrating Buddhist perspectives on science and technology. Employing a mixed-methods approach, the study utilizes purposive sampling to select participants. Data is gathered through interviews, surveys, and document analysis. Analysis involves thematic coding and triangulation of findings. Initial results indicate a significant correlation between teacher workload, student performance, and the incorporation of Buddhist principles into science and technology education. These findings contribute to understanding how educational practices can be enhanced by bridging academic rigor with holistic philosophies, fostering a more balanced approach to learning and preparing students for the demands of the modern world.